PENGARUH BUDAYA ORGANISASI DAN MOTIVASI KERJA TERHADAP KINERJA PRAJURIT MELALUI KEPUASAN KERJA PRAJURIT PADA SATUAN KAPAL SELAM KOARMADA II - jurnalpps pps; Ady Soanata; Indra Prasetyo; Nugroho Mardi Wibowo (Jurnal Manajerial Bisnis, 2020)
This study is to determine how the conditions of organizational culture, work motivation, job satisfaction and performance of soldiers in the Submarine Unit of Koarmada II Surabaya. Furthermore, to see and analyze both partially and simultaneously performance, work motivation, job satisfaction, organizational culture, work motivation on performance at the Koarmada II Submarine Unit Surabaya. This type of research is an explanatory study with a sample of 82 soldiers in the Koarmada II Submarine Unit in Surabaya. The results showed that the variables of job satisfaction, organizational culture and work motivation on achievement amounted to 0.648 or 64.8%, while the remaining 0.352 or 35.8% other variables were not included in this study. The direct effect of the variable job satisfaction on employees is obtained by the Beta Standard Coefficient value of 0.279 and the significance value is 0.014. The satisfaction level of the job satisfaction variable on the soldier's performance is 0.2792 = 0.078 or 7.8%. Organizational culture has a significant effect on job satisfaction at the Koarmada II Surabaya Submarine Unit.Keywords: job satisfaction, organizational culture, work motivation, soldier performance